A big data Bayesian approach to earnings profitability in the S&P 500 - Tan, Teik Kheong; Merouane, Lakehal-Ayat (Emerald Publishing Limited, 2018)
The impact of volatility crush can be devastating to an option buyer and results in a substantial capital loss, even with a directionally correct strategy. As a result, most volatility plays are for option sellers, but the profit they can achieve is limited and the sellers carry unlimited risk. This paper aims to demonstrate the dynamics of implied volatility (IV) as being influenced by effects of persistence, leverage, market sentiment and liquidity. From the exploratory factor analysis (EFA), they extract four constructs and the results from the confirmatory factor analysis (CFA) indicated a goodmodel fit for the constructs.